Budaya Islam Nelayan Pesisir Utara Lamongan Jawa Timur - Nurdin, Ali (IBDA` : Jurnal Kajian Islam dan Budaya, 2020)
This study aims to understand and describe the religious traditions of fishers in Pesisir Utara Lamongan, East Java in their daily realities that shape transcendental experiences. This study uses a phenomenological approach to describe the experience of the religious practice of the fishers in Pesisir Utara Lamongan, East Java. The data were collected through in-depth interviews and were analyzed using flow models with the viewpoint of symbolic interaction theory that explored the symbolic meaning of the fishers’ behavior. The results of this study described that the daily experience of the fishers in social life is constructed in three religious practices, namely monotheism, social life, and worship. The monotheistic dimension of the fishers is transformed from offerings to monotheism. The dimension of the social life of the fishers is constructed based on the monotheism of Nahdlatul Ulama (NU) and Muhammadiyah teachings. The dimension of worship of the fishers is portrayed in the practice of religious prayer, fasting, and going to wise persons formed by the results of interaction with the surrounding social world. Penelitian ini bertujuan untuk memahami dan mendeskripsikan tradisi keagamaan nelayan Pesisir Utara Lamongan, Jawa Timur dalam realitas keseharian yang membentuk pengalaman transendental. Penelitian ini menggunakan pendekatan fenomenologi untuk mendeskripsikan pengalaman praktik keagamaan nelayan Pesisir Utara Lamongan, Jawa Timur. Pengumpulan data dilakukan dengan wawancara mendalam dan dianalisis dengan menggunakan model alir dengan sudut pandang teori interaksi simbolik yang mengeksplorasi makna simbolik perilaku nelayan. Hasil penelitian ini mendeskripsikan bahwa pengalaman keseharian nelayan dalam kehidupan sosial terkonstruksi dalam tiga praktik keagamaan yaitu dimensi tauhid, kehidupan sosial, dan ibadah. Dimensi tauhid nelayan mengalami transformasi dari sesajen ke tauhid. Dimensi kehidupan sosial nelayan dikonstruksi berbasis tauhid ajaran Nahdlatul Ulama (NU) dan Muhammadiyah. Dimensi ibadah nelayan terpotret dalam praktik keagamaan sholat, puasa, dan pergi ke orang pintar yang dibentuk atas hasil interaksi dengan dunia sosial di sekitarnya.